Stratigraphy, structure and geodynamic evolution of the Paleozoic rocks in the Cordillera del Viento (37º S latitude, Andes of Neuquén, Argentina) - Giacosa, R.; Allard, J.; Foix, N.; Heredia, N. (Journal of Iberian Geology, 2014)
The Pre-Andean Paleozoic substrate from the Cordillera del Viento anticline is a polyorogenic basement composed of two groups of preorogenic rocks with different stratigraphy and deformation. The oldest set consists of pre-Late Devonian metasedimentary rocks belonging to the Guaraco Norte Formation. The upper set is formed by the thick volcano-sedimentary sequence of the Carboniferous Andacollo Group. This group is composed from bottom to top of the silicic volcanic rocks of the Arroyo del Torreón Formation (early Carboniferous) and the marine sedimentary rocks of the Huaraco Formation (late Carboniferous) developed in an extensional basin. Both formations are locally separated by minor syn-extensional unconformities. The relationship between the metamorphic rocks of the Guaraco Norte Formation and the volcano-sedimentary sequence of the Andacollo Group is not observed, but we inferred a major angular unconformity associated with the Late Devonian-early Carboniferous Chanic orogeny. The main Chanic structures are tight vertical and subvertical folds with slight W-WSW vergence, formed under low-grade metamorphic conditions, with the development of a pervasive axial-plane cleavage (S1), affected by a disjunctive crenulation cleavage (S2). In the early Permian, during the San Rafael orogeny of the Gondwanan orogenic cycle, deformation occurred under very low-grade to non-metamorphic conditions. The main structures are thrusts and associated folds that are re-folded by the Cordillera del Viento anticline, related to the Andean orogeny. The WNW-oriented and SSW-vergent folds are associated with an incipient axial-plane cleavage in the pyroclastic rocks and pencil lineation in shales. The pre-Andean Paleozoic basement rocks are intruded and unconformably covered by early Permian to Early Triassic? granitoids and silicic volcanic rocks from the Huingancó volcanic-plutonic Complex (equivalent to the Choiyoi Group), establishing the beginning of the Andean orogenic cycle in this region.